Hubungan Bilateral Indonesia-Malaysia: Review Buku - Ali Maksum (Universitas Diponegoro, 2016)
This book examines the relationship between Indonesia and Malaysia. This book was decended from the dissertation at the University of Western Australia. The aim of this book was to understand Malaysian foreign policy towards Indonesia from the perspective of constructivism. The author argued that non-material elements are crucial in explaining the relationship between two countries. The author mentioned ideational factors such as culture, ethnic, elite perception, identity, leadership, nationalism, as well as religion.Keywords: Indonesia, Malaysia, foreign policy, constructivism